The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1415-54192008000500010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de métodos radiográficos utilizados na localização vertical de sítios eleitos para instalação de mini-implantes

Abstract: OBJETIVO: avaliar a efetividade de métodos de diagnóstico por imagem utilizados na localização vertical de sítios eleitos para inserção de mini-implantes. METODOLOGIA: a amostra foi composta de quatro pacientes, nos quais foram estabelecidos 32 sítios inter-radiculares, na região posterior, para instalação de mini-implantes, sítios estes representados por orifícios preenchidos com guta-percha em moldeiras de acetato (PCg - ponto de contato das coroas dentárias na moldeira de acetato; PIg - ponto de inserção do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
2
Order By: Relevance
“…Even though it is not possible to conclude which of them would present the highest accuracy, and also considering the limitations of 2D image overlapping and distortion, results suggest that there is no advantage of one technique over the other, at least in a mesiodistal evaluation of the OMI position. Differently, Matzenbacher et al 15 demonstrated that PAR had a greater degree of distortion than bitewing radiography; however, this study compared vertical measurements for the location of the implantation site of OMI (place where the head of the device will be located). This study did not evaluate horizontal measurements, nor did the region related to the OMI tip.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Even though it is not possible to conclude which of them would present the highest accuracy, and also considering the limitations of 2D image overlapping and distortion, results suggest that there is no advantage of one technique over the other, at least in a mesiodistal evaluation of the OMI position. Differently, Matzenbacher et al 15 demonstrated that PAR had a greater degree of distortion than bitewing radiography; however, this study compared vertical measurements for the location of the implantation site of OMI (place where the head of the device will be located). This study did not evaluate horizontal measurements, nor did the region related to the OMI tip.…”
Section: Discussionmentioning
confidence: 87%
“…A sample size calculation was performed based on the reported results of a previous published article. 15 A α error probability of 0.05 and power of 0.8 were used for an estimate of difference between PAR and VBW in 45% of the cases, resulting in a sample size of at least 20 mini-implants. G*Power 3.1.9 software ( http://www.gpower.hhu.de/en.html ) was used for calculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…posicionador radiográfico cirúrgico (PRC) acoplado ao 3D GR radiografias periapicais são freqüentemente utilizadas como avaliação do posicionamento final dos mini-implantes no septo inter (KURODA, et al, 2007b;GARFINKLE, et al, 2008;MOON, et al, 2008) representam um exame preciso, desde que tenham sido executadas de forma padronizada, e, preferencialmente, com o auxílio de posicionadores ou de guias (BARROS, 2008;BARROS, et al, In press 2007) este tipo de radiografia não tem sido considerado adequado para avaliar a posição eleitos para instalação de mini-implantes, baseados na interpretação de imagens radiográficas devem possuir aparelho, técnica e processamento (ZONTINE, 1974;EISNER, 1998 (BARROS, 2008;BARROS, et al, In press 2007). Entretanto, para avaliar a posição , diferentemente da tomografia computadorizada e a radiografia interproximal, técnicas consideradas seguras para avaliar tal posicionamento dos mini-implantes (MATZENBACHER, et al, 2008). Chen et al (CHEN, Y.H., et al, 2008) acreditam que as radiografias apresentam baixa sensibilidade para diagnosticar contato dos mini-implantes às raízes dentárias adjacentes (55,3% com especificidade de 100%), promovendo diagnósticos equivocados de contato radicular e necessitando de comprovação através de análise histológica.…”
Section: Método Radiográficounclassified
“…ao tipo e à técnica cirúrgica, tornando-se um recurso cada vez mais seguro e padronizado. Entretanto, a literatura apresenta poucos estudos que avaliam as técnicas radiográficas disponíveis para orientação do profissional no momento do planejamento, instalação e posicionamento final dos mini-implantes (MATZENBACHER, et al, 2008).…”
Section: Método Radiográficounclassified